Entrepreneurship Education as a Catalyst for Poverty Reduction and National Security in Nigeria - Olalekan, Oduntan Kemi; Gbeminiyi, Adedayo Temitayo (NIU Journal of Social Sciences; Vol 4 No 4 (2018): KIU Journal of Social Sciences, Vol. 4 No. 4, December 2018, 2019)
The study examined entrepreneurship education as catalyst for poverty reduction and national security in Nigeria using time series data over the period 1995 to 2015. While entrepreneurship education (proxy by index of industrial production) served as independent variable, GDP growth rate, poverty rate and government expenditure served as explanatory variables. Using ordinary least square multiple regression analysis, the paper revealed that GDP growth rate is positively related to index of industrial production while the poverty rate and government expenditure on national security have negative signs which is an indication of the high rate of unemployment in Nigeria as many able bodied youth and graduates are not employed and as such, depended on the working population for survival which increases the rate of abject poverty. The paper suggest that government should not only integrate entrepreneurship education as an integral part of the curriculum across all levels of education but should also establish skills acquisition centres across the country to reduce youth unemployment stem down the rate of poverty and insecurity in the country. Keywords: Entrepreneurship Education, Poverty Reduction, GDP Growth, Industrial Production, Government Expenditure, Poverty Rate, Skills Acquisition, National Security.